Water, people and food in the Mekong River Basin - Cook, Simon E. (2009)
Three factors will drive great change in the Mekong area:1) Population is expected to increase from the current 6 0million to more than 90 million in 2050. 2) The proportion of urban dwellers will rise from about 20 % to about 40 %. Economic growth is around 4.5 % per annum.3) With an annual average rainfall of over 7km3 per capita, the major issues concern not total water availability, but the impact of changed flows on ecology, fish production, access to water and food security.